Modernité et culture du rire - Alain Vaillant (Cahiers de Narratologie)
As part of the historical poetics of literary forms, this article intends to analyse the singularity of laughter in nineteenth-century French « modernité » (modernity), to explain how it appeared after the French revolution and to precise its links with the media-centered culture whose center becomes at this time Paris. A short commentary of the two main French literary texts about laughter (the Preface de “Cromwell” by Victor Hugo and the essay De l’essence du rire by Charles Baudelaire) will also enable to estimate the truly literary invention in which laughter is at the same time the means and the aim. Thanks to this esthetical redefinition of laughter, the comical merges with lyricism – with an ironical lyricism which is the main contribution of the modernity to the art of laughter.